Rumen microbes from African ruminants can degrade Acacia angustissima diamino acids - McKie, M.R.; Brown, D.L.; Melesse, A.; Odenyo, A.A. (Elsevier, 2004)
This work examined the ability of microorganisms from African ungulates to degrade 4-N-acetyl-2,4-diaminobutyric acid (ADAB) found in A. angustissima leaves, as well as purified ADAB and diaminobutyric acid (DABA). These microorganisms were taken from the rumens of bush duiker, eland, impala, Grant's gazelle, hartebeest, Thompson's gazelle, Ethiopian goat, Kenyan goat, an Ethiopian sheep adapted to Acacia angustissima ingestion and from the hindgut of zebra. Dried A. angustissima leaves, 3 g/L ADAB or 3 g/L DABA were incubated with medium containing rumen or hindgut fluid. Degradation was measured using ammonia and volatile fatty acid production and substrate disappearance as indices. Individual microbial species were isolated from samples showing substrate degradation. Incubation of A. angustissima leaf with rumen fluids from the bush duiker and from a sheep slowly adapted to A. angustissima produced more gas (32.27 mL/100 g DM ± 1.15; 31.25 mL/100 g DM ± 2.17) than with fluid from other animals. Early substrate degradation was observed with samples incubated with bush duiker rumen fluid. The most total volatile fatty acids were produced by samples incubated with rumen fluid from Grant's gazelle, followed by impala and bush duiker (79.67 ± 4.35 µmol/mL, 78.21 ± 11.3 and 68.80 ± 4.49 µmol/mL, respectively). Samples incubated with rumen fluids from the impala, Thomson's gazelle and Grant's gazelle produced the most ammonia (39.44 ± 2.81 mmol/L, 39.05 ± 1.83 and 37.67 ± 2.13 mmol/L). Rumen fluid taken from an impala degraded more ADAB than the other sources, leaving only 4.17 µM residual ADAB. Rumen fluid from the hartebeest was completely ineffective and left all of the ADAB substrate undegraded. The adapted sheep rumen fluid degraded 0.980, the Grant's gazelle rumen fluid 0.922 and the impala rumen fluid only 0.101 of the ADAB. Eight ADAB-tolerant bacterial strains were isolated. Individually, these isolates were not able to substantially degrade ADAB. However, a mixture of all eight ADAB-tolerant bacterial isolates degraded 0.827 of the ADAB. Most DABA-tolerant bacterial strains were not able to degrade DABA. Only isolates from an adapted sheep, from a Kenyan goat and a Thomson's gazelle degraded DABA to a significant extent (0.283, 0.202 and 0.169, respectively). Mixing DABA-tolerant strains did not improve DABA degradation.